2014
DOI: 10.1038/labinvest.2014.59
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of MYB oncogene in transformed adenoid cystic carcinomas reveals distinct pathways of tumor progression

Abstract: Adenoid cystic carcinomas can occasionally undergo dedifferentiation, a phenomenon also referred to as high-grade transformation. However, cases of adenoid cystic carcinomas have been described showing transformation to adenocarcinomas that are not poorly differentiated, indicating that high-grade transformation may not necessarily reflect a more advanced stage of tumor progression, but rather a transformation to another histological form, which may encompass a wide spectrum of carcinomas in terms of aggressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…The importance that MYB activation, either through gene alterations or MYB‐NFIB fusions, has in ACC oncogenesis has been underscored by recent whole‐exome sequencing studies of head and neck ACCs, which showed an otherwise ‘quiet’ mutational landscape with very few genetic aberrations. These findings indicate that activating MYB aberrations are probably driving these tumors …”
Section: Discussionmentioning
confidence: 99%
“…The importance that MYB activation, either through gene alterations or MYB‐NFIB fusions, has in ACC oncogenesis has been underscored by recent whole‐exome sequencing studies of head and neck ACCs, which showed an otherwise ‘quiet’ mutational landscape with very few genetic aberrations. These findings indicate that activating MYB aberrations are probably driving these tumors …”
Section: Discussionmentioning
confidence: 99%
“…However, RT‐PCR cannot detect cases of gene fusion without transcript formation since translocation of other genetic sequences to the noncoding flanking sites of the MYB gene may lead to aberrant fusion and atypical MYB transcriptional activation . The implementation of next generation sequencing may circumvent these issues based on its ability to detect MYB and/or NFIB gene rearrangement or variant gene fusions although it may overlook cases of ACC with copy number gains or gene insertions/deletions . The availability and implementation of these studies in most laboratories may be limited by cost, increased turn‐around time, and technical challenge.…”
Section: Discussionmentioning
confidence: 99%
“…7 The implementation of next generation sequencing may circumvent these issues based on its ability to detect MYB and/or NFIB gene rearrangement or variant gene fusions although it may overlook cases of ACC with copy number gains or gene insertions/deletions. 20 The availability and implementation of these studies in most laboratories may be limited by cost, increased turn-around time, and technical challenge. Recent whole genome sequencing studies have revealed novel driver mutations involving the MYB homologue, MYBL1, identifying a novel MYBL1-NFIB fusion as a result of translocation of 8q and 9p in t(6;9)-negative and t(6;9)-positive with MYB-NFIB fusion negative ACC.…”
Section: Discussionmentioning
confidence: 99%
“…MYB is associated with the development of tumours, including leukaemia, pancreatic cancer, breast cancer and prostate cancer (16)(17)(18). However, whether MYB is associated with the development and metastasis of SACC is not clear (19).…”
Section: Introductionmentioning
confidence: 99%